Vulnerability of children and adolescents in the use of social networks and parental mediation - Maria de Araújo, Emanuela; Paulo Viana Figueiredo, Pedro (Revista Pesquisas e Práticas Psicossociais, 2017)
With the fast dissemination of technologies of information and communication, social networks occupy a fundamental role in the life of young people, changing the means of communication and interaction – being the principal reason of internet access among them. In view of the large number of children and adolescents who have a profile in these networks according to recent research (Cgi.br, 2012, 2013, 2014), one of the problems relates to the difficulty of caregivers to mediate the use of those technologies, with the need to assist their children in the responsible use of these tools and to understand their benefits and risks. Therefore, we analyzed which strategies parents have been using to supervise the use of those tools by their children. Twelve semi-structured interviews were conducted with parents of children and adolescents in the age ranging from nine to seventeen years old, residents of the city of Recife, located in Pernambuco, Brazil. The interviews were analyzed according to the Discursive Social Psychology (Potter, 1996; Potter & Whetherell, 1987). We conclude that, for the participants, social networks are important mechanisms in the processes of social interaction. However, they still report difficulties in what they consider risky or not for their children and mediation strategies occur in different ways and without following a specific orientation. Keywords: Social Networks. Risk. Parental mediation. Discursive Social Psychology.